The Brigade Renderer: A Path Tracer for Real-Time Games - Jacco Bikker; Jeroen van Schijndel (International Journal of Computer Games Technology)
We present the Brigade renderer: an efficient system that uses the path tracing algorithm to produce images for real-time games. We describe the architecture of the Brigade renderer, and provide implementation details. We describe two games that have been created using Brigade.